Polyaromatic hydrocarbons for anolyte applications in lithium based secondary batteries - Lunchev, Andrey V. (2018)
A possible way to overcome some limitations of Li-ionic batteries, including slow rate of charge and discharge, high cost, and safety issues, is to use liquid based electrodes due to their fast ion transport, high solubility of active components, and complete elimination of such solid based electrode drawbacks as metal dendrite formation. While some types of non-solid based cathodes (air or catholytes like iodide/triiodode system) have already been investigated, utilization of liquid based anodes (anolytes) is a relatively new concept. One promising approach for a liquid based anode uses solvated electron solutions (SES) formed by the reaction between polycyclic aromatic hydrocarbons (PAH) and alkali metals in organic solvents. This concept has been successfully demonstrated with biphenyl and naphthalene as the PAH. Considering that it should be possible to optimize the ability of PAHs to form Li SES that are suitable for anolyte applications by varying their size and substituents or heteroatoms in the aromatic rings, this thesis represents a systematic study on formation, electrical and electrochemical properties of Li SES based on a number of polyaromatic systems: p-terphenyl, anthracene, 1,3,5-triphenylbenzene and its derivatives, triphenylene, hexaphenylbenzene and hexa-peri-hexabenzacoronene derivatives, and isomeric phenyl- and bipyridines. The maximum achieved Li:PAH ratio for p-terphenyl is 2.4:1 and for anthracene is 2:1. The ratios of Li:PAH = 2:1 for both the molecules were achieved in more concentrated Li SES prepared from suspensions of these PAHs in THF. A Li:PAH ratio of 4:1 can be achieved for 1,3,5-triphenylbenzene. However, the aromatic system degrades when the ratio is above 2:1. Electron donating groups in 1,3,5-triphenylbenzene framework have a negative effect on Li SES formation due to destabilization of the resulting anion. A Li:PAH ratio of 4:1 was achieved for triphenylene in a dilute solution, but could not be obtained with higher concentrations of the PAH. Although hexaphenylbenzene does not react with lithium, it was shown that a hexa-peri-heabenzocoronene derivative can react with 6 mole equivalents of lithium or potassium. For the isomeric phenylpyridines, the achieved Li:PAH ratio is 2:1 except for 4-phenylpyridine, which forms a precipitate when the Li:PAH ratio is larger than 1:1. For all the Li SES based on bipyridines and biphenyl in HMPA, the Li:PAH ratios are lower than 2:1. Among the PAH solutions of ~0.1 M concentration, p-terphenyl, triphenylene, and anthracene based Li SES demonstrate the highest conductivity, which is higher than the value for Li SES based on naphthalene of the same concentration. For p-terphenyl and anthracene, conductivity significantly increases upon the increase of PAH concentration. The conductivity of Li SES prepared from suspensions of these materials in THF is the highest among Li SES studied in this project and comparable to the maximum achieved for naphthalene and biphenyl. In the case of 1,3,5-triphenylbenzene derivatives, it was found that incorporation of alkyl chains significantly increase the solubility of PAH, but makes negative effect on conductivity. The majority of tested Li SES demonstrate decrease in conductivity upon temperature increase, which is similar to metals and ammonia based Li SES. However, some of the studied Li SES with high concentration of Li and those prepared in HMPA demonstrate the opposite behavior. The values of OCP (E) vs Li+/Li for studied Li SES in THF lie in the range of 0.6 – 0.9 V. The lowest value of OCP was obtained for 1,3,5-triphenylbenzene (0.47V), while Li SES in HMPA generally demonstrate high values (>1.2V). Based on the E(T) data, ΔS and ΔH were calculated. It was shown that for p-terphenyl and anthracene the correlation between ΔS and Li:PAH ratio (x) is quasi linear (tested for x>0.5). In general, ΔS increases with the increase of x for all the studied Li SES. The lowest values of ΔS were obtained for phenylpyridines while the highest values are reached for Li SES in HMPA. The calculated ΔS values for various Li SES are much higher than those for solid state electrodes used in LIB. The ΔH(x) exhibits more complex correlation than ΔS(x). For the case of p-terphenyl, the results of quantum chemical modelling demonstrate the feasibility of formation of dimeric structures, which can be related to this more complex behaviour. The obtained results allowed to clarify the correlations between structures of PAH and properties of the resulting Li SES, and demonstrate the potential feasibility of using the Li SES based on some of the studied materials such as p-terphenyl, anthracene, triphenylene, 1,3,5-triphenylbenzene and 3-phenylpyridine as anolytes in secondary batteries. During the course of the project, a new approach for synthesis of 5,7-diazapentacene derivatives and precursors was developed. The structure and electronic properties of these novel materials were characterized. These compounds may find potential applications in both Li SES and OFET.